APLIKASI NILAI MENGGUNAKAN METODE PROTOTYPING PADA DI SMK FARMASI BINA MEDIKA - Sopiah, Nyimas; Suyanto, Suyanto (JURNAL ILMIAH MATRIK, 2018)
Sekolah Menengah Kejuruan (SMK) Bina Medika is one of Vocational High School in Pharmacy in Palembang. The academic system is primarily about value, so far still conventionally done. Assessment is given by the teacher to the homeroom to be written into student report cards. The problem that often happens is often a mistake in writing student grades. Therefore, it will be made the application of student value in supporting the academic system in the vocational school using PHP-based programming language website. The purpose of the study is to generate value applications so as to reduce the errors of writing value-based websites. Development method used is Prototyping method. Keywords: User Centered Design, Prototyping, Value